Antibiotic Prescription Patterns And Disease Trends In The NICU Of A South Indian Tertiary Care Hospital - Inamdar, Shirish; Rincy Joy, Rincy Joy; Devarshi, Priyanka. N. (Journal of Neonatal Surgery, 2025)
Background: Neonate refers to an infant in the first 28 days after birth. They are special group of population who are more susceptible to nosocomial infections due to underdeveloped immunity. The study was conducted to identify the disease spectrum and also to analyze the prescription pattern of antibiotics at our neonatal intensive care unit. Antibiotics are one of the most prescribing drugs in Neonatal Intensive Care Units (NICU). Objectives: To assess the prescription pattern of antibiotics and disease pattern in in Neonatal Intensive Care Units (NICU). Materials and Methods: This is a prospective observational study conducted at Basaveshwara Medical College& Hospital, Chitradurga. a period of six months in Neonatal intensive care unit. Results: A total of 100 patient’s data were collected from neonatal intensive care unit, Majority of diseases occurs in 1-10 days age group (76%). 24 were diagnosed with respiratory distress syndrome, 20 patients with low birth weight, 15 patients having birth asphyxia,13 patients were small for gestational age,12 patients had intra uterine growth retardation,12 were diagnosed with sepsis,6 cases were meconium aspiration syndrome. Out of 195 antibiotics prescribed 97 drugs are Penicillins, 89 Cephalosporins, 6 Aminoglycosides and 3 Meropenems. Conclusion: The study concludes that most commonly occurring disease in NICU is respiratory distress syndrome (RDS) and low birth weight (LBW). Penicillins and Cephalosporins are commonly prescribed antibiotics rarely Aminoglycosides and Meropenems.